I have this DEQ: $$3x^2y+2xy+y^3+(x^2+y^2)y^{'}=0$$ and I want to find an integrating factor to make it exact. I derived the formula to do so as $$\mu^{'}=\frac{\mu(M_y-N_x)}{N}$$ I know that $M_y=3x^2+2x, N_x=2x,N=x^2+y^2$, so I can substitute them in the above equation$$\frac{\mu^{'}}{\mu}=\frac{3x^2}{x^2+y^2}$$However, I don't know how to solve for $\mu$ at this point. Can anyone give me a hint on how to proceed from here?

  • $\begingroup$ Apparently this method isn't apply here. $\endgroup$ – Nosrati Feb 9 '17 at 20:44

$$(3x^2y+2xy+y^3)dx+(x^2+y^2)dy=0$$ Suppose $F(x,y)$ be an integrating factor so that $\quad (3x^2y+2xy+y^3)F(x,y)dx+(x^2+y^2)F(x,y)dy\quad$ be a total derivative.

If so, the relationship between the partial derivatives must be :

$$\frac{\partial }{\partial y} \big( (3x^2y+2xy+y^3) F(x,y)\big)=\frac{\partial }{\partial x}\big( (x^2+y^2)F(x,y)\big)$$

$$(3x^2+2x+3y^2)F+(3x^2y+2xy+y^3) \frac{\partial F}{\partial y} = (2x)F + (x^2+y^2)\frac{\partial F}{\partial x}$$ After simplification : $$(3x^2y+2xy+y^3) \frac{\partial F}{\partial y} - (x^2+y^2)\frac{\partial F}{\partial x}+3(x^2+y^2)F=0$$ The goal is not to solve this PDE for the general solution, but only to find a particular solution (as simple as possible).

Obviously, if we try $F$ function of $x$ only, the simplification is big : $$\frac{\partial F}{\partial y}=0 \quad\to\quad -\frac{dF}{dx}+3F=0$$ $$F=e^{3x}$$ So, a integrating factor is $\quad e^{3x}$ .

I suppose that you can take it from here to find the general solution of the ODE (on the form of implicit equation): $$e^{3x}\left(y^3+3x^2y\right)=C$$ If you want the solution on explicit form, solve the cubic equation for $y$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.